2005
DOI: 10.1021/es048622y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recovery of PCB-Contaminated Sediments at the Lake Hartwell Superfund Site:  PCB Dechlorination. 1. End-Member Characterization

Abstract: Under anaerobic conditions, such as those typically found in buried sediments, the primary metabolic pathway for polychlorinated biphenyls (PCBs) is reductive dechlorination in which chlorine removal and substitution with hydrogen by bacteria result in a reduced organic compound with fewer chlorines. Vertical sediment cores were collected from Lake Hartwell (Pickens County, SC) and analyzed in 5-cm intervals for 107 PCB congeners in a total of more than 280 samples from 18 sediment cores and surface samples. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 22 publications
5
48
0
Order By: Relevance
“…Because we have examined all PCB congeners, this study has included all those that were found to be ubiquitous, toxic, or potentially toxic. This study considered all congeners that would result from all possible routes: intentional, or incidental, chlorinated biphenyl syntheses, for example, coupling reactions, and as byproducts, and environmental alteration products by selective vaporization or absorption, and reductive dechlorination during metabolism, photochemical reaction, combustion, and chemical remediation [44][45][46][47]. Rather than relying on the common method of total or combined PCB quantification, or the electron capture detector (for high sensitivity), this study employed technology that provided excellent separation of 196 PCB congeners that were either present in or absent from Aroclor formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Because we have examined all PCB congeners, this study has included all those that were found to be ubiquitous, toxic, or potentially toxic. This study considered all congeners that would result from all possible routes: intentional, or incidental, chlorinated biphenyl syntheses, for example, coupling reactions, and as byproducts, and environmental alteration products by selective vaporization or absorption, and reductive dechlorination during metabolism, photochemical reaction, combustion, and chemical remediation [44][45][46][47]. Rather than relying on the common method of total or combined PCB quantification, or the electron capture detector (for high sensitivity), this study employed technology that provided excellent separation of 196 PCB congeners that were either present in or absent from Aroclor formulations.…”
Section: Resultsmentioning
confidence: 99%
“…RSC can suggest "where" potential sources are located by following concentration gradients while ACF can confirm "what" potential source fingerprints are present. As described in previous PCB forensic studies (Johnson et al, 2000;Magar et al,2005), both source fingerprints as well as weathering patterns (due to differences in solubility, dechlorination, etc.) can often be discerned using these statistical analyses.…”
Section: Test Designmentioning
confidence: 87%
“…PCBs also behave quite differently in the environment and many factors need to be considered in addition to the most common weathering factors; interpretation methods need to be modified and new data interpretation and analysis considerations need to be developed (Johnson et al, 2006). Emerging PCB fingerprinting techniques have successfully been applied at a few sites in the US (Johnson et al, 2000;Emsbo-Mattingly and Durell, 2003;Magar et al, 2005;Johnson et al, 2007), but there is a need to more fully develop, demonstrate, and validate the utility of fingerprinting PCB contamination. Additional discussions and comparisons for some analytical techniques (both RSC and ACF) are presented in Section 8, and comparisons for some statistical interpretation techniques (receptor models) are shown in Section 6.…”
Section: Advantages and Limitations Of The Technologymentioning
confidence: 99%
See 2 more Smart Citations